RETRACTED: Factors influencing capital stucture on F&B company which implementing sustainable environmental green practise in Indonesia - Tasyahuda Amalia Dewi; Najmudin Najmudin; Shaferi Intan; Laksana Rio Dhani (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001